Gender Equality: Women’s Rights in Review 2020 - United Nations Women (United Nations, 2020)
2020 marks the 25th anniversary of the adoption of the Beijing Platform for Action. It also marks the first time that progress on the implementation of the Platform is reviewed in light of the 2030 Agenda for Sustainable Development, adopted in 2015. This report therefore takes an integrated approach to reporting on progress, gaps and challenges related to the advancement of gender equality and women’s rights across six dimensions that link the Platform’s critical areas of concern and the Sustainable Development Goals. It finds that there have been important gains since the adoption of the Beijing Platform in 1995, but that progress towards gender equality has stalled and even reversed in some areas in recent years. Across the globe women’s movements, energized by young feminists at the helm, are challenging slow and piecemeal progress and are impatient for systemic change. World leaders can learn from the ways in which these movements work across silos and political boundaries, seeing their work to advance the rights of women and girls as inextricably linked to the achievement of economic, social and environmental justice for all. The report features their voices that must be heard and acted upon. The report also highlights catalytic policies and programmes under each of the six dimensions as well as a number of cross-cutting strategies that can accelerate the implementation of the entire Platform for Action for this generation and the next.